2008
DOI: 10.1080/10447310802142243
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Method for Measuring the Emergence of New Ideas in Information Discovery

Abstract: While sometimes the task that motivates searching, browsing, and collecting information resources is finding a particular fact, humans often use information resources in intellectual and creative tasks that can include comparison, understanding, and discovery. Information discovery tasks involve not only finding relevant information, but also seeing relationships among collected information resources, and developing new ideas. Our hypothesis is that how information is represented impacts the magnitude of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 33 publications
0
34
0
Order By: Relevance
“…Kerne et al extended these metrics for tasks involving information-based ideation and discovery [20].…”
Section: Creative Cognitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Kerne et al extended these metrics for tasks involving information-based ideation and discovery [20].…”
Section: Creative Cognitionmentioning
confidence: 99%
“…Users create information compositions to answer open-ended divergent thinking questions, such as developing a research topic or planning a family vacation. It has been shown that authoring information compositions stimulates emergence of new ideas on information-based ideation tasks [20].…”
Section: Mixed-initiative Information Compositionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kerne et al developed a quantitative methodology for the evaluation of information-based ideation tasks, invoking a battery of mutually independent ideation metrics to assess creative products [11]. Webb and Kerne refined methods for calculating the novelty and variety information-based ideation metrics [18].…”
Section: Prior Workmentioning
confidence: 99%